English at workplace: a quantitative report on communication apprehension among Malaysian employees / Mohd Zulfadli Mat Husin - Mat Husin, Mohd Zulfadli (Universiti Teknologi MARA, 2022)
Oral communication had been regarded as one of the important elements especially in Malaysian workplace context and the use of English language had been deemed to be the necessary requirement for employees. Based on series of literature review, only a few studies had been done toward examining communication apprehension issue using English within Malaysian workplace context. With the aim of investigating English oral communication apprehension among Malaysian employees, the study adopted quantitative approach and use PRCA-24 as the main instruments to 352 respondents. From PRCA-24, four communicative events were measured which group discussion, meeting, conversation and public were speaking. Overall, Malaysian employees recorded a moderate level of CA using English at workplace. In addition, government employees are more apprehensive compare to their counterpart. Both private and government employees recorded higher level of CA during public speaking and meeting. In relation to demographic variables, gender, job sector and highest education levels were found to be significant in influencing level of CA among Malaysian employees whilst both age and years of service were not. The study inferred some important findings that could help in understanding English communication apprehension at workplace and Malaysian employers (private and government) need to consider continuous professional development to further enhancement English communication competency of their employees resulting in lowering CA level.